2022
DOI: 10.1002/app.52691
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different polyolefin copolymers on properties of melt mixed polypropylene blends

Abstract: Polypropylene (PP) is an affordable plastic commodity but lacks massive use in engineering applications given its limited mechanical properties including significantly low impact strength. In this work, three polyolefin-based copolymers including ethylene-octene random block (Engage, E), ethylene-octene multiblock (Infuse, I), and ethylene-propylene copolymer (Versify, V) were blended with PP. It was found that the V copolymer was miscible while the rests were immiscible in the PP matrix. Mechanical testings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…In separate studies of 50:50 LDPE/iPP blends compatibilized with 5 wt % of an EPDM copolymer, Vervoot et al and Fortelný et al reported approximately 6- and 3-fold increases in impact strength, respectively. In another study, Radonjič et al reported a 4-fold improvement in the impact strength for 80:20 LDPE/iPP recycled blends compatibilized with 10 wt % of an EPR or EPDM copolymer . These findings are consistent with impact resistance increasing with the introduction of a rubbery phase capable of absorbing energy, thereby preventing failure at the PE/PP phase boundary.…”
Section: Review Of Blendsmentioning
confidence: 79%
See 1 more Smart Citation
“…In separate studies of 50:50 LDPE/iPP blends compatibilized with 5 wt % of an EPDM copolymer, Vervoot et al and Fortelný et al reported approximately 6- and 3-fold increases in impact strength, respectively. In another study, Radonjič et al reported a 4-fold improvement in the impact strength for 80:20 LDPE/iPP recycled blends compatibilized with 10 wt % of an EPR or EPDM copolymer . These findings are consistent with impact resistance increasing with the introduction of a rubbery phase capable of absorbing energy, thereby preventing failure at the PE/PP phase boundary.…”
Section: Review Of Blendsmentioning
confidence: 79%
“…In part, this is due to the chemical similarities of branched polyolefins (e.g., LLDPE and LDPE), the covalent copolymerization of olefins (e.g., PP copolymers), and the intentional blending of virgin resins (e.g., impact modified iPP). For example, reactor blending and postreactor blending of iPP with ethylene- co -propylene rubber (EPR), ethylene- co -propylene- co -diene monomer (EPDM), and other amorphous polyolefins is a common practice for enhancing impact strength, toughness, and processability. , It should be noted that although compatibilization to improve the performance and consistency of secondary plastics is an urgent need, the technologies covered herein also apply to virgin blends, which can result in superior properties, new applications, and material reduction.…”
Section: Introductionmentioning
confidence: 99%